Employer expectations for business graduate communication and thinking: an investigation conducted in Singapore and Perth. - Forde, Patrick J. (Curtin University, 2000)
In Australia, the employment destinations of new graduates are surveyed annually and descriptions of successful employment have become an indicator of quality within the higher education sector. The expectations that employers hold for graduate generic skills are of interest, therefore, to graduates and the institutions they attended. Communication and thinking are recognised widely as the most important generic skills, however the application of these skills will occur in the workplace where academic skills may not be totally appropriate. In addition, many graduates of Australian institutions; e.g., international students, are likely to be employed by foreign organisations. Therefore, not only is the workplace a very different environment to academia but graduates could be expected to satisfy the expectations of employers working in culturally different environments.This investigation describes the expectations participating Singaporean and Perth employers held for recently graduated business graduates with particular attention given to graduate communication and thinking. The exploratory research used interviews and surveys to assemble contextual descriptions of employer expectations. The interview data was used to construct a questionnaire that was administered across a larger sample of employers to see whether the surveys corroborated the interview findings. Contextual descriptions of the communication and thinking capabilities that the Singaporean and Perth employers expected recent business graduates to possess are provided by this study. Gaps between employer expectations and perceptions of graduate ability are discussed, together with useful graduate characteristics. During data analysis five themes were noted and they have been used to propose a model of employer expectations. Finally, seven recommendations for professional practitioners have been suggested and a list of employer concerns is provided.